2009
DOI: 10.1128/iai.01441-08
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Hck, Fgr, and Lyn Tyrosine Kinases Augments Lung Innate Immune Responses toPneumocystis murina

Abstract: Src family tyrosine kinases (SFKs) phosphorylate immunotyrosine activation motifs in the cytoplasmic tail of multiple immunoreceptors, leading to the initiation of cellular effector functions, such as phagocytosis, reactive oxygen species production, and cytokine production. SFKs also play important roles in regulating these responses through the activation of immunotyrosine inhibitory motif-containing inhibitory receptors. As myeloid cells preferentially express the SFKs Hck, Fgr, and Lyn, we questioned the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…We have previously reported that mice deficient in the myeloid Src family kinases Hck, Fgr, and Lyn (Src TKO mice) demonstrated an increase in alternatively activated macrophages (28), which we have demonstrated to have an enhanced capacity to kill P. murina (28,29). Because Src TKO mice are more resistant to P. murina lung infection (29), we questioned whether this observation correlated with Mmp12 expression.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 82%
“…We have previously reported that mice deficient in the myeloid Src family kinases Hck, Fgr, and Lyn (Src TKO mice) demonstrated an increase in alternatively activated macrophages (28), which we have demonstrated to have an enhanced capacity to kill P. murina (28,29). Because Src TKO mice are more resistant to P. murina lung infection (29), we questioned whether this observation correlated with Mmp12 expression.…”
Section: P Murina Lung Exposure Results In the Induction Of Mmp12mentioning
confidence: 82%
“…Unexpectedly, however, mice triple deficient in the SFKs Hck, Fgr, and Lyn (Src TKO mice) had augmented innate lung clearance of P. murina that correlated with both an increased lung inflammatory response and a greater ability of Src TKO AMs to kill P. murina in vitro (27). Because AMs are critical effector cells required for P. murina lung clearance (7), and because Src TKO AMs killed P. murina more efficiently (27), we hypothesized that Src TKO AMs would be hyperresponsive to P. murina stimulation resulting in increased inflammatory mediator production. Surprisingly, the opposite was true, as Src TKO AMs produced lower amounts of multiple mediators known to be produced by AMs in response to P. murina, including G-CSF, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…RELM-α is a cysteine-rich secreted protein originally identified in the lung (44) and subsequently observed to be expressed by macrophages, eosinophils, epithelial cells, and endothelial cells (44,45). RELM-α stimulates production of MCP-1 (46) and IL-6 (46), both of which we have previously reported to be increased in the lungs of P. murina-infected Src TKO mice (27). RELM-α can also bind to F4/80 + cells (45), which we also reported to be recruited in greater numbers to the lungs of P. murina-infected Src TKO mice (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations